(untitled) (International Journal of Innovative Research in Engineering & Management, 2022)
A teacher is a nation builder, and learning is the best attribute of the nation builders. A teacher develops all profession by moulding the students. The world is transforming at a more excellent pace, and we need to upgrade in many dimensions. A teacher should always be on his toes to specify the changes in every discipline and adopt them in their teachings to enrich the students with suitable skills. In this regard, this study is taken up to list out the factors encouraging a teacher to learn. The study is conducted on teachers in Andhra Pradesh who expressed that professional development is the most critical influencer for learning.